HSV-2 incidence by sex over four age periods to age 38 in a birth cohort. (13th December 2013) - Dickson, Nigel; Righarts, Antoinette; van Roode, Thea; Paul, Charlotte; Taylor, Janette; Cunningham, Anthony L
Abstract : Objectives: To examine herpes simplex virus type 2 (HSV-2) incidence over four periods to age 38 in a birth cohort, and to compare risks for men and women, taking into account sexual behaviour. Methods: At ages 21, 26, 32 and 38, participants in the Dunedin Multidisciplinary Health and Development Study were invited to provide serum for HSV-2 serology, and information on sexual behaviour. HSV-2 incidence rates were calculated for four age periods, and comparisons made by sex and period, taking into account number of sexual partners. Results: By age 38, 17.3% of men and 26.8% of women had ever been seropositive for HSV-2. Incidence peaked for women from age 21 to 26 (19.1 per 1000 person-years) and men from age 26 to 32 (14.1 per 1000 person-years); it fell markedly for both from age 32 to 38 (5.1 and 6.8 per 1000 person-years for men and women, respectively). Overall risk was significantly higher for women: adjusted incidence rate ratio 1.9 (95% CI 1.4 to 2.7); the sex difference was most marked from age 21 to 26 (3.4, 95% CI 1.9 to 6.3). Conclusions: Our findings are consistent with a greater biological susceptibility to HSV-2 among women, and with the increasing risk to the early/mid-20s for women and late 20s/early 30s for men, being driven by an increasing pool of prevalent infection. The reduced risk in the mid-30s is consistent with declining infectivity of long-term prevalent infections.